(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
Despite their increasing importance in sedimentology and palaeoecology, non-geniculate coralline algae remain virtually overlooked in Slovenia. Though these plants are present or even abundant in the Cretaceous and Cainozoic strata, they have never been studied in detail with notable exception of corallines from the Lower Oligocene beds in the area of Gornji Grad. Poljšica pri Podnartu is another locality where Lower Oligocene beds are exposed, considered as equivalent to the former. The studied profile consists of pebbly limestone, mudstone, sandstone and limestone. Limestones contain abundant non-geniculate coralline algae. Nine species from six genera of these corallines have been identified: Lithoporella melobesioides (Foslie) Foslie, 1909, Neogoniolithon contii (Mastrorilli) Quaranta et al., 2007, Spongites sp., Lithothamnion sp. 1, Lithothamnion sp. 2, Mesophyllum sp. 1, Mesophyllum sp. 2, Mesophyllum sp. 3 and Sporolithon sp. Some of these species are described from Slovenia for the first time.